Grain yield and quality of common bean cultivars in response to nitrogen - Aires, Bruno Corrêa [UNESP]; Soratto, Rogério Peres [UNESP]; Guidorizzi, Fernando Vieira Costa [UNESP] (UNESP - Universidade Estadual Paulista, 2019)
Nitrogen (N) is the nutrient most required by common bean, and the response to N fertilization may be variable among genotypes. The objective of this work was to evaluate the N nutrition, grain yield, grain size, and crude protein concentration of common bean cultivars in response to topdressing N rates. Two experiments were conducted on a Typic Rodudalf, under two growth conditions (“dry” and “rainy” seasons). A randomized complete block design with a 7 × 4 factorial arrangement and four replicates was used. The treatments consisted of seven cultivars (Pérola, BRS Ametista, BRS Notável, IPR Campos Gerais, IPR Tangará, IAC Formoso, and IAC Imperador) and four N rates (0, 35, 70, and 140 kg ha-1). The experiments were analyzed jointly. The application of N did not affect the cycle, plant population, and number of grains per pod, but increased the leaf N concentration, number of pods per plant, grain size, and grain yield, regardless of the cultivar. The responses of common bean cultivars to N rates varied according to the growth condition, with response to N only in the “rainy” season experiment, under conditions of lower N and higher C/N ratio in the straw of the preceding crop. The crude protein concentration in the grains was influenced in an inconsistent manner by the factors studied.
Keywords: Genotype; Grain size; Nitrogen fertilization; Phaseolus vulgaris; Protein